(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Yashada is one of the Sapta dhatu, which is chemically Zn, Yashada bhasma is used therapeutically in many diseases like Prameha, Pandu, Vatavyadi etc., in the form of Bhasma (ZnO). Objectives: To prepare Yashada bhasma and its physico-chemical analysis of Yashada bhasma. Materials and Methods: Yashada was subjected Samanya Shodhana, Vishesha Shodhana and Jarana as per Rasatarangini. Yashada marana was done as per Rasayana sara. Bhasma was subjected to physico-chemical analysis which mainly included classical Bhasma parikshas like Rekhapurnata, Varitara, Unama, Nischandrata etc and modern parameters like Acid Insoluble Ash, pH, Total Ash value etc and advanced analytical techniques like XRD, SEM and AAS. Results: After 1st Puta pale yellow colored Yashada bhasma passed classical Bhasma parikshas. In classical reference two Puta are mentioned so, the 2nd Puta was given. XRD reports shows major peaks which were identified as Zinc oxide (ZnO) compound. Hence indicates complete transformation of metal to Bhasma form. Scanning electron microscopy in Yashada Bhasma after 2nd Puta the particle size ranging from 5-10μm. AAS reports shows zinc percentage of 77.08% after 2nd Puta. Conclusion: Pale yellow coloured Yashada bhasma was prepared after two Gaja putas which passed the classical Bhasma parikshas.